2014
DOI: 10.1186/1476-4598-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of muscarinic receptor subtype gene ablation on murine colon tumorigenesis reveals association of M3R and zinc finger protein 277 expression in colon neoplasia

Abstract: BackgroundM3 and M1 subtype muscarinic receptors are co-expressed in normal and neoplastic intestinal epithelial cells. In mice, ablating Chrm3, the gene encoding M3R, robustly attenuates intestinal tumor formation. Here we investigated the effects of Chrm1 gene ablation, alone and in combination with Chrm3 ablation.MethodsWe used wild-type, Chrm1-/-, Chrm3-/- and combined Chrm1-/-/Chrm3-/- knockout (dual knockout) mice. Animals were treated with azoxymethane, an intestine-selective carcinogen. After 20 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 40 publications
(71 reference statements)
2
34
0
Order By: Relevance
“…Our findings suggested that M3 in PDAC could play a significant role in the invasive process in vivo. Recent investigations into the functional role of M3 in carcinomas have demonstrated that the expression of M3 augmented cell motility on extracellular matrix components47 and promoted tumor growth in mice16,17 in addition to its effect on cancer cell proliferation 18. These findings support our hypothesis that M3 in PDAC could play a role in the invasive process and its expression could be a more malignant phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings suggested that M3 in PDAC could play a significant role in the invasive process in vivo. Recent investigations into the functional role of M3 in carcinomas have demonstrated that the expression of M3 augmented cell motility on extracellular matrix components47 and promoted tumor growth in mice16,17 in addition to its effect on cancer cell proliferation 18. These findings support our hypothesis that M3 in PDAC could play a role in the invasive process and its expression could be a more malignant phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…This may be considered speculative as acetylcholine is a non-selective M3R agonist. Nonetheless, we believe this conclusion is justified based on the strong body of evidence that M3R regulates these signaling cascades in human colon cancer cells [13, 46, 48], the identification of M3R as the primary M3R subtype expressed in both HT-29 and H508 colon cancer cells [17], and the key finding in animal models that M3R deficiency robustly attenuates the development of colon neoplasia whereas M1R deficiency has no effect [11, 18, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the five muscarinic receptor subtypes, M1R, M3R, and M5R are conditional oncogenes when expressed in cells capable of proliferation [8]. M3R are expressed widely in the gut and both M3R and CHRM3 , the gene encoding its expression, are over-expressed in colon cancer [7, 9–11]. We previously showed that M3R activation governs key hallmarks of colon cancer progression including cell proliferation, survival, migration, and invasion [1217].…”
Section: Introductionmentioning
confidence: 99%
“…We showed divergent effects of MR subtype gene ablation on murine colon tumorigenesis. [ 45 ] Although AOM-treated M3R-deficient mice had fewer and smaller colon tumors than control WT mice, reductions in colon tumor number and size were not observed in M1R-deficient and dual M1R/M3R-deficient mice. Microarray and real-time PCR analyses revealed a possible role for zinc finger protein (Zfp) 277 expression in mediating these different phenotypes.…”
Section: Mr Signaling In Crc and Disease Progressionmentioning
confidence: 99%